If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 12 + -6a = 28 Reorder the terms: 12 + 3a + -6a = 28 Combine like terms: 3a + -6a = -3a 12 + -3a = 28 Solving 12 + -3a = 28 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3a = 28 + -12 Combine like terms: 12 + -12 = 0 0 + -3a = 28 + -12 -3a = 28 + -12 Combine like terms: 28 + -12 = 16 -3a = 16 Divide each side by '-3'. a = -5.333333333 Simplifying a = -5.333333333
| 2[2x(4-3)]=3(6-1) | | -9(7z-5)+6(-7z+1)= | | 4x-2(x-2)=-8+5x+5 | | (7v-2)(v+7)=0 | | 10x-3+84=10x+39 | | .32+.23x=1.01 | | 5-(2x+6)=-5 | | -6(8r+9)+9(9r-8)= | | 6+16=6-16 | | -9(-3x+5)+8(-2x+2)= | | 5-20=10-60 | | lnx+ln(x-6)=5 | | 1760=40x | | 2[2x(4-3)]=-3x(6-1) | | Q=4p-110 | | 21=42+7r | | 3x+6+2x+9=90 | | -14xy+32xy= | | 15h+1= | | -3n+11=-2n-1 | | 2x+8+11x+1= | | 46=x+(2x-5)(3x+6) | | 7x+6x-57=76-6x | | 9-8x=-(5x+5)-5x | | 46=x+(2x-5)(3x-6) | | 46=x+(2-5)(3x-6) | | 4k+20=-8 | | x^2+5+5x+25=180 | | -7+-70=-5-2+75 | | -5(-4s-4)-4(-4s-7)= | | 5x+3x=5x-19 | | 4b+4(1-3b)=-3b+39 |